Potential Makroalga on the Beach Karapyak to the Development of Power Stations Biogas Seaweed (Seawees Biogas Power Plant) - Nuryadin, Egi (Jurnal Sains Dasar, 2018)
Energy resources in Indonesia need to use alternative energy. According to the world energy board, energy use tends to increase by 50 percent by 2020. Indonesia is an archipelagic country that has vast and tropical waters and this makes indonesia has a high potential for developing renewable energy from macroalgae. Karapyak beach area is a coastal area in southestern west java that has abundant water biodiversity and high potential for the development of marine biotechnology. Abundant macroalgae in the karapyak beach is Gracilaria Sp, which can be used as biogas. Then this study was conducted to determine the potential of Gracilaria Sp, as an alternative material for biogas which would later become an alternative energy power plant. Biogas quality determination can be seen from the content of CO2, CH4, C2H5OH, dan CH3OH found in Glacilaria Sp. So that the potential for developing seaweed biogas electricity can be seen from the results of this study.